Socrate o dello specchio. Strategie di scrittura nell’Apologia e nell’Alcibiade - Palumbo, Lidia (Plato Journal, 2020)
Through a mention to the Middle Platonists and a reference to a late antique text that presents a comparison between Plato and the Demiurge, I set out to show just one of those rhetorical strategies that have been used by the author Plato to give his writings the unity and consistency that make the corpus a kosmos, a living animal, like the universe. After having identified among the rhetorical strategies the one that uses examples and explained what such a strategy means, I analyse the Platonic use of the example of the mirror identified with Socrates in two writings, the Apology of Socrates and the Alcibiades I.